2011
DOI: 10.1029/2011jd015918
|View full text |Cite
|
Sign up to set email alerts
|

Variations in organic aerosol optical and hygroscopic properties upon heterogeneous OH oxidation

Abstract: [1] Measurements of the evolution of organic aerosol extinction cross sections (s ext ) and subsaturated hygroscopicity upon heterogeneous OH oxidation are reported for two model compounds, squalane (a C 30 saturated hydrocarbon) and azelaic acid (a C 9 dicarboxylic acid). For both compounds, the s ext values at 532 nm increase substantially as the particles undergo oxidation, exhibiting a logarithmic increase with OH exposure. The increase in s ext correlates with both an increase in the particle oxygen to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
195
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(211 citation statements)
references
References 60 publications
13
195
3
Order By: Relevance
“…This results in a lower critical supersaturation at which the aerosol can behave as a cloud condensation nuclei [Petters and Kreidenweis, 2007]. There is additional evidence that the aerosol O/C is correlated with aerosol scattering cross-sections [Cappa et al, 2011]. Thus, accurately modeling aerosol O/C is important not only to test our understanding of SOA formation mechanisms, but also for predictions of the aerosol direct effect (scattering incident radiation) and the aerosol indirect effect (cloud formation).…”
Section: Comparison Of Model Soa O/c and Mass With Measurementsmentioning
confidence: 99%
“…This results in a lower critical supersaturation at which the aerosol can behave as a cloud condensation nuclei [Petters and Kreidenweis, 2007]. There is additional evidence that the aerosol O/C is correlated with aerosol scattering cross-sections [Cappa et al, 2011]. Thus, accurately modeling aerosol O/C is important not only to test our understanding of SOA formation mechanisms, but also for predictions of the aerosol direct effect (scattering incident radiation) and the aerosol indirect effect (cloud formation).…”
Section: Comparison Of Model Soa O/c and Mass With Measurementsmentioning
confidence: 99%
“…However, O:C versus m r trends in one direction for the two lower HC/NO x ratios; m r s increase with decreasing O:C whereas the highest HC/NO x ratio (lowest NO x ) has the opposite trend. Cappa et al (2011) showed in a previous study that heterogeneous OH oxidation of the squalene and azelaic acid increases refractive index with addition of oxygen (increasing O:C). However, our other cases (HC/NO x = 6.6,14) show the opposite relationship, suggesting that O:C ratio is not the only factor controlling the refractive index.…”
Section: Effect Of the Hc/no X Ratiomentioning
confidence: 99%
“…In addition, the optical cross sections of the multiple-charged particles are typically greater than that of the singly charged particles, with a fractional contribution to the optical cross section that is greater than their fractional abundance. A common method used in CRDS retrievals of complex refractive index is to calculate and subtract the extinction due to doubly and triply charged particles from the total measured extinction (Fierz-Schmidhauser et al, 2010;Cappa et al, 2011;Flores et al, 2012). The disadvantage of this method is that it requires an assumed refractive index for the multiple-charged particles.…”
Section: Determination Of Complex Refractive Index As a Function Of Wmentioning
confidence: 99%